Pelatihan Kompetensi Overhauld Engine Di SMK Ma’arif Nu Talang - Mukhamad Khumaidi Usman; Amin Nur Akhmadi; Faqih Fathurozzak (CV. Multi Kreasi Media, 2023)
Along with the continuous use of motorized vehicles and long service life, the vehicle will experience damage such as an abnormal sound of low compression or the release of thick smoke in the pot caused by damaged piston rings or scratched cylinder blocks, which makes engine oil burn into smoke that comes out of the vehicle, this can be fixed with engine Overhaul, where Overhaul itself in English is a very thorough inspection. This community service activity aims to provide knowledge about engine Overhaul, provide training on the engine Overhaul process with engine component disassembly methods, provide training and understanding of the use of personal protective equipment and hazards during engine Overhaul practice. The purpose of this service is expected that students can understand how the gasoline motor works, be able to analyze the beginning of damage to the vehicle, and perform engine Overhauls properly and correctly. The result of this training is that students can identify machine damage and can repair machines correctly.